Efficacy and safety of canagliflozin in Japanese patients with type 2 diabetes: a randomized, double‐blind, placebo‐controlled, 12‐week study1. Issue 12 (14th July 2013) - Inagaki, N.; Kondo, K.; Yoshinari, T.; Maruyama, N.; Susuta, Y.; Kuki, H.
Abstract : Aims: We examined the efficacy, safety and tolerability of canagliflozin, a sodium glucose co‐transporter 2 inhibitor, in Japanese patients with type 2 diabetes (T2DM) undergoing diet and exercise therapy. Methods: Patients aged 20–80 years with T2DM diagnosed ≥3 months previously, and HbA1c of 6.9–9.9% were randomized to 50, 100, 200 or 300 mg canagliflozin or placebo once daily for 12 weeks. The primary and secondary endpoints were changes in HbA1c, fasting plasma glucose (FPG), urinary glucose/creatinine and postprandial glycaemic parameters following a meal test. The safety assessments included adverse events (AEs) and clinical laboratory tests. Results: Overall, 383 patients were randomized to receive either placebo (n = 75), or 50 mg (n = 82), 100 mg (n = 74), 200 mg (n = 77) or 300 mg canagliflozin (n = 75). At week 12, significant reductions in HbA1c were observed in all canagliflozin groups relative to placebo (−0.61, –0.80, –0.79 and −0.88% for 50, 100, 200 and 300 mg, respectively, versus +0.11% for placebo; all, p < 0.01). FPG and postprandial glycaemic parameters improved significantly in the canagliflozin groups. Body weight was significantly decreased by canagliflozin. No deaths or drug‐related serious AEs were reported. There was no dose‐dependent increase in the incidence of AEs in the canagliflozin groups. The incidence of hypoglycaemia was low; episodes were not severe or dose dependent. Canagliflozin did not affect serum creatinine levels or the urinary albumin/creatinine ratio. Conclusions: Treatment with canagliflozin for 12 weeks significantly improved glycaemic control and reduced body weight in Japanese patients with T2DM. Canagliflozin was well tolerated.